Cracking of Concrete, its Healing and Simultaneous Monitoring - Kaur, Nimratpal (Curtin University, 2022)
This thesis addresses premature deterioration of concrete built infrastructure by introducing intrinsic healing. Emulating living organisms, a healing technique for concrete has been developed using live bacteria. The healing has been monitored using an advanced ultrasonic technology. An innovative method for testing long term durability of concrete is developed. The thesis demonstrates that the healing impedes deterioration of concrete, especially reinforcement corrosion.